Circulation of RSV Subtypes A and B Among Mexican Children During the 2021–2022 and 2022–2023 Seasons - Zárate, Selene; Taboada, Blanca; Torres-Rivera, Karina; Bautista-Carbajal, Patricia; Garcia-León, Miguel Leonardo; Tabla-Orozco, Verónica; Juárez-Tobías, María Susana; Noyola, Daniel E.; Martínez-Arce, Pedro Antonio; Espinosa-Sotero, Maria del Carmen; Martínez-Aguilar, Gerardo; Rojas-Larios, Fabian; et al. (Pathogens (Basel), 2025)
Respiratory syncytial virus (RSV) remains a leading cause of pneumonia in young children in Mexico and worldwide. To investigate RSV dynamics in Mexico, we conducted a multicenter study from August 2021 to July 2023 in six hospitals across five States, analyzing respiratory samples from children under five years with pneumonia. Multiplex RT-PCR identified 203 RSV-positive cases, of which 123 were RSV-B and 80 RSV-A. Interestingly, 77% of the collected samples showed evidence of coinfection with other respiratory pathogens, with rhinovirus, Haemophilus influenzae, and Streptococcus pneumoniae being the most common. Also, RSV-B dominated in 2021–2022, whereas RSV-A prevailed in 2022–2023, mirroring trends observed in the United States. Sequences of the genes encoding G and F proteins showed that RSV-A lineages were more diverse, with A.D.1, A.D.1.8, and A.D.5.2 being frequently detected. In contrast, nearly all RSV-B sequences belonged to lineage B.D.E.1. Finally, ancestral state inference suggests repeated introductions from the USA and other North American countries, with limited evidence of sustained local circulation. These findings show different trends in RSV circulation between two consecutive seasons and the importance of genomic surveillance to monitor RSV diversity, evaluate vaccine impact, and inform public health strategies in Mexico’s evolving post-pandemic respiratory virus landscape.